Enhancement of the chemical stability of nanoemulsions loaded with curcumin by unsaturated mannuronate oligosaccharide. (15th July 2023) - Bi, Decheng; Li, Meiting; Yao, Lijun; Zhu, Nanting; Fang, Weishan; Guo, Wushuang; Wu, Yan; Xu, Hong; Hu, Zhangli; Xu, Xu
Graphical abstract: Highlights: MOS was studied as a stabilizer in nanoemulsion preparation for the first time. MOS-CUR was slightly more stable than water-CUR. MOS-CUR had improved antioxidant activity than free curcumin and water-CUR. The curcumin loaded in MOS-CUR had an improved bioavailability than in water-CUR. Abstract: Unsaturated mannuronate oligosaccharide (MOS) is an acidic oligosaccharide prepared from alginate-derived polymannuronate by enzymatic depolymerization, followed by double bond formation between C-4 and C-5 at the nonreducing end. In this study, MOS was used as a stabilizer to fabricate O/W nanoemulsions loaded with curcumin (MOS-CUR) for the first time. The results revealed that the MOS-CUR showed small droplet sizes and narrow size distributions and was slightly more stable than normal oil-in-water (O/W) curcumin nanoemulsions (water-CUR). Additionally, MOS can improve the superoxide anion scavenging ability and iron ion reducing ability of the curcumin nanoemulsion system. Although the digestion behaviour of MOS-CUR and water-CUR was similar, the bioavailability of curcumin in MOS-CUR was significantly higher than that in water-CUR. All these results indicated that MOS could be used as a stabilizer for preparing nanoemulsions to easily encapsulate labile nutrients and to enhance the bioavailability and antioxidant capacity of these nutrients.